Analisis Tingkat Kesegaran Ikan Konsumsi Di Pelabuhan Perikanan Tenda Berdasarkan Uji Organoleptik Dan Derajat Keasaman (pH) - Muh. Alsere Bardian Sahaba; Wila Rumina Nento; Fernandy M. Djailani; Sumrin Sumrin; Mita Alvionita (Jambura Fish Processing Journal, 2026)
Fish is the primary source of animal protein for the Indonesian people, particularly in coastal areas such as Gorontalo Province. The freshness of fish is a key factor in ensuring food quality and safety. This study aimed to evaluate the freshness levels of fish for human consumption at Tenda Fishing Port in Gorontalo Regency based on organoleptic parameters and pH values. The samples consisted of four fish species: mackerel (Rastrelliger kanagurta), blue lolosi (Caesio caerulaurea), layang fish (Decapterus sp.), and yellow selar (Selaroides leptolepis), with four fish of each species collected using purposive sampling. Organoleptic testing was conducted by 25 semi-trained panelists in accordance with SNI 2729:2013, evaluating parameters such as appearance, gills, mucus, texture, and odor on a scale of 1-9. pH measurements were taken using pH indicator paper on the dorsal flesh. The results showed that all four fish species received organoleptic scores above 7, indicating that they were fresh and fit for consumption according to SNI 2729:2013 standards. pH measurements showed that mackerel and yellow mackerel had pH levels of 6,5-6,9, while blue lolosi and layang fish had pH levels of 6,2-6,5, which is consistent with the condition of fish in the rigor mortis phase. The correlation between high organoleptic scores and a pH range of 6,2-6,9 indicates that the fish for human consumption traded at Tenda Fishing Port were still fresh at the time of sampling. Consistent implementation of a cold chain system is necessary to maintain the quality of the fish until it reaches consumers.